Diversidad de la regeneración natural e incremento dasométrico de especies forestales en áreas de restauración ecológica de la reserva Numbami en la provincia Zamora Chinchipe - Sánchez Contento, Mayra Alexandra (2021)
In 2012, the Nature and Culture International Foundation (NCI) began an ecological restoration process under a reforestation scheme with native species and the release of natural regeneration established in 23 ha of degraded grasslands in the Jamboé reserve, located in the Numbami sector, Zamora Chinchipe province. Within this context, the present study was developed in order to know the current state of ecological restoration in the Numbami Reserve through the characterization of natural regeneration and the dasometric increase of forest species both planted and released in the ecological restoration areas. Six sampling plots of 400 m2 were established with nested plots of 25 m2 and 4 m2 for evaluation of natural regeneration in the category of latizales, saplings and seedlings respectively. Within natural regeneration, the ecological parameters and the Shannon diversity index were analyzed. On the other hand, within the 400 m2 plots, the dasometric increase in diameter and height of the reforested and released species was evaluated by comparing it with data obtained in a pilot inventory in 2017. Forty-nine naturally regenerated species belonging to 45 genera and 29 families were identified; the most ecologically important species according to the ecological parameters evaluated were Miconia astroplocama, Platymiscium sp. and Palicourea sp, showing that they are pioneer species that develop in disturbed lands, either due to their adaptability or due to the large number of regenerated seeds. Shannon index reflected a state of medium diversity within a period of seven years without anthropic intervention. Regarding the reforested and released species, a better survival of the reforested species was evidenced with 86.3% compared to 73.96% of those released. Heliocarpus americanus and Piptocoma discolor species showed better growth in both height and diameter, concluding that in addition to being heliophytic species suitable for colonizing open spaces and giving successional formation for the other species, they are important to initiate ecological restoration processes. Keywords: natural regeneration, dasometric increase, restoration